Academic Performance and Critical Thinking Among Secondary Students: A Conceptual Exploration of Disposition and Demographic Influences - Chin, Ying Ying; Loo , Fung Lan (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
Malaysia’s performance in international assessments such as the Programme for International Student Assessment (PISA) and the Trends in International Mathematics and Science Study (TIMSS) remains a significant concern, with national scores consistently falling behind those of many other participating countries. The 2022 PISA report reveals that Malaysia ranks among the top 5 countries globally with the largest declines in test scores across all 3 core subjects: Reading, Mathematics, and Science. Despite substantial reforms implemented by the Malaysian government including a strong emphasis on 21st-century learning to foster critical and higher-order thinking skills (HOTS), students’ performance in international assessments has yet to show meaningful improvement. Critical thinking skills (CTS) are essential for students in the 21st century, as they enhance cognitive abilities, support improved academic achievement in both national and international standardised assessments, and equip learners to meet the demands of an increasingly complex world. These skills also play a pivotal role in ensuring national competitiveness and adaptability, particularly in the context of the 4th Industrial Revolution. This concept paper explores the mediating role of Critical Thinking Disposition (CTD) in the relationship between CTS and academic performance among Form 2 students in Malaysia. It also investigates the moderating effect of demographic factors on the relationships among CTS, CTD, and academic achievement. The researcher posits that CTS alone may not directly influence academic performance; rather, CTD serves as a key mediator, while demographic factors act as moderators that shape these relationships across diverse learner contexts.